A novel LUAD prognosis prediction model based on immune checkpoint-related lncRNAs - Liu, Yang; Yu, Mingyang; Cheng, Xuechao; Zhang, Xingshu; Luo, Qian; Liao, Sijin; Chen, Zhongzheng; Zheng, Jianhao; Long, Kaijun; Wu, Xingwei; Qu, Wendong; Gong, Ming; et al. (Frontiers in Genetics, 2022)
Lung adenocarcinoma (LUAD) is a malignant disease with an extremely poor prognosis, and there is currently a lack of clinical methods for early diagnosis and precise treatment and management. With the deepening of tumor research, more and more attention has been paid to the role of immune checkpoints (ICP) and long non-coding RNAs (lncRNAs) regulation in tumor development. Therefore, this study downloaded LUAD patient data from the TCGA database, and finally screened 14 key ICP-related lncRNAs based on ICP-related genes using univariate/multivariate COX regression analysis and LASSO regression analysis to construct a risk prediction model and corresponding nomogram. After multi-dimensional testing of the model, the model showed good prognostic prediction ability. In addition, to further elucidate how ICP plays a role in LUAD, we jointly analyzed the immune microenvironmental changes in LAUD patients and performed a functional enrichment analysis. Furthermore, to enhance the clinical significance of this study, we performed a sensitivity analysis of common antitumor drugs. All the above works aim to point to new directions for the treatment of LUAD.